(untitled) (Proceeding of SINERGY, 2026)
Environmental degradation and environmental crime represent complex challenges that extend beyond ecological damage, affecting economic sustainability, social justice, and cultural values within society. In Indonesia, the enforcement of environmental criminal law remains fragmented and sectoral, involving multiple institutions with overlapping authorities. This institutional configuration has resulted in ineffective law enforcement, prolonged legal processes, and limited accountability for large-scale environmental crimes, particularly those involving corporate actors. This article examines the politics of law surrounding the establishment of an Environmental Crime Commission as a form of multiparadigm legal innovation aimed at supporting sustainable development. By integrating legal, economic, social, and cultural paradigms, this study moves beyond conventional normative-repressive approaches to environmental law enforcement. The research employs a normative legal methodology using statutory, conceptual, and comparative approaches to analyze the urgency, legitimacy, and strategic value of creating a specialized environmental law enforcement body. The findings demonstrate that the establishment of an Environmental Crime Commission constitutes an institutional innovation capable of addressing structural weaknesses in existing enforcement mechanisms. From an economic perspective, effective enforcement contributes to sustainable resource management and the internalization of environmental costs. Socially, it strengthens environmental justice and public access to justice. Culturally, it fosters a shift in legal culture toward greater ecological awareness and responsibility. This study concludes that the Environmental Crime Commission represents a multiparadigm innovation that not only enhances the effectiveness of environmental criminal law enforcement but also functions as an instrument for economic, social, and cultural transformation in line with the principles of sustainable development.